Improving tourism and hospitality services - Laws, Eric, 1945- (CABI, 2004)
This book analyses the nature and quality of service experiences for the tourism and hospitality industry's clients, its staff and others affected by its operations. It draws together several approaches for the study of tourist satisfaction, equating this with quality in tourism and hospitality services. It examines situations that have caused problems resulting in customer dissatisfaction. Other examples show how some of the industry's most successful organizations succeed in providing profitable services that their customers enjoy. Also discussed is the significance of the marketing function in hospitality and tourism, particularly as it relates to customer expectations of service standards and consumer buying decisions. Other issues in the effective management of services are examined. The book has 8 chapters and a subject index. It also includes an appendix in the form of a set of slides for a management development workshop summarizing the main points in this book.